ANALYSIS OF THE OCEANOGRAPHIC CONDITIONS OF MEOSBEKWAN ISLAND (RAJA AMPAT DISTRICT) FOR THE SUITABILITY OF SEAWEED CULTIVATION - Lanuru, Mahatma; Amri, Khairul; Mashoreng, Supriadi; Dahlan, Dahlan; Paulangan, Yunus (Hasanuddin University, 2023)
Seaweed cultivation is an alternative community livelihood that potentially helping to reduce pressure on coral reefs in the area of Raja Ampat Archipelago. This study was aimed to conduct an oceanographic analysis of the waters of Meosbekwan Island (Raja Ampat Regency) for the suitability of seaweed cultivation. Oceanographic data collection was carried out at three points (M1, M2, and M3) on the western side of Meosbekwan Island. Analysis of suitability for aquaculture was initiated with an analysis of key parameters, i.e., depth, protection and shipping traffic. The suitability analysis was followed by an analysis of the oceanographic parameters of the waters by weighting them using a ranking system. Furthermore, the final stage of suitability analysis was to evaluate the feasibility level of seaweed cultivation. The results showed that the depth of the waters on the western side of Meosbekwan Island ranged from 1.3 m – 5.8 m with an average depth of 1.5 m in the south (M1), 2.2 m in the middle (M2), and 3.9 m to the north (M3). Wave height during the study ranged from 0.1 – 0.3 m with an average value of 0.25 m at all points. The velocity of the water currents ranged from 0.08 – 0.25 m/s. The salinity of the waters was relatively homogeneous (30 - 31 o/oo). Water temperature also has small and relatively homogeneous variations with a range of 30 - 31˚C. The brightness of the waters ranged from 2.5 – 3.5 m. The bottom of the waters on the west side of Meosbekwan Island generally consists of coarse sand, rubble, and seagrass vegetation Enhalus acoroides and Cymodocea sp. In general, the oceanographic conditions of the waters are suitable for the life and growth of seaweed. The results of the location suitability evaluation indicated that the waters on the western side of Meosbekwan Island were technically feasible to serve as a location for seaweed cultivation.